PENINGKATAN KESEHATAN PERIODONTAL IBU HAMIL DALAM UPAYA MENGURANGI RESIKO BAYI DENGAN BERAT BADAN LAHIR RENDAH - I KOMANG EVAN WIJAKSANA; Lambang Bargowo; Shafira Kurnia Supandi (Universitas Airlangga, 2020)
During the Covid-19 pandemic, there was an increase in pregnancy rates in East Java. Besides efforts to suppress pregnancy rates, it is also necessary to ensure the health of the mother and fetus in order to be born healthy. The prevalence of periodontal diseases in pregnant women is high, while the dental visit of pregnant women is low. Periodontal disease is one of the risk factors of preterm birth as well as low-birth-weight (LBW) infants. In this community service, socialization held through lecture methods, QnA, discussion and self-practice procedures to maintain oral health procedures. The goal is to improve pregnant women's knowledge of the importance of dental and oral care, especially periodontal tissue during pregnancy and enhance skills of pregnant women in detecting early symptoms of periodontal diseases and to perform oral dental care independently at home. The knowledge and skills of pregnant women can be improved during this community service. By healthy periodontal tissue and teeth, it is expected that the risk of LBW infants and also preterm birth can be decreased.abstrakSelama masa pandemi Covid-19, terjadi peningkatan tingkat kehamilan di Jawa Timur. Selain usaha menekan tingkat kehamilan, perlu juga dipastikan kesehatan ibu dan janin agar lahir dengan sehat. Prevalensi kelainan periodontal pada ibu hamil tinggi sementara kunjungan ibu hamil ke dokter gigi rendah. Penyakit periodontal merupakan salah satu faktor resiko bayi lahir prematur dan juga berat badan lahir rendah (BBLR). Dalam pengabdian masyarakat ini dilakukan sosialisasi melalui metode ceramah, tanya jawab, diskusi dan praktek mandiri prosedur menjaga kesehatan rongga mulut. Tujuannya adalah meningkatkan pengetahuan ibu hamil mengenai pentingnya perawatan gigi dan mulut khususnya jaringan periodontal selama kehamilan dan meningkatnya ketrampilan ibu hamil dalam mendeteksi gejala awal kelainan periodontal dan cara melakukan perawatan gigi mulut mandiri di rumah. Pada pengabdian masyarakat ini pengetahuan dan ketrampilan ibu hamil dapat ditingkatkan. dengan jaringan periodontal dan gigi serta rongga mulut yang sehat, diharapkan resiko BBLR maupun kelahiran prematur dapat diturunkan.